2020
DOI: 10.1108/jfbm-05-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of research on human resource management in family firms: analyzing the past; preparing for the future

Abstract: PurposeThis paper explores the field of human resource management (HRM) in family firms, assessing the evolution of this research through a four-domain model that reflects the relationships between cognitions, actions and performances associated with organizational choices.Design/methodology/approachThe authors have performed a bibliometric review of 363 peer-reviewed papers from over the past four decades (1976–2016) in order to provide activity indicators for the overall phenomenon and systemize the entire b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 127 publications
0
11
0
1
Order By: Relevance
“…Bisnis keluarga biasanya dibedakan berdasarkan dimensi strategis dan organisasi mereka, serta keterlibatan keluarga dalam visi, kepemilikan, manajemen atau tata kelola perusahaan [36]- [39]. Hal ini mengarah pada perbedaan signifikan bisnis keluarga karena berkaitan dengan hubungan timbal balik yang kuat antara keluarga dan perusahaan.…”
Section: Hasil Dan Pembahasan Bisnis Keluarga Vs Bisnis Non-keluargaunclassified
“…Bisnis keluarga biasanya dibedakan berdasarkan dimensi strategis dan organisasi mereka, serta keterlibatan keluarga dalam visi, kepemilikan, manajemen atau tata kelola perusahaan [36]- [39]. Hal ini mengarah pada perbedaan signifikan bisnis keluarga karena berkaitan dengan hubungan timbal balik yang kuat antara keluarga dan perusahaan.…”
Section: Hasil Dan Pembahasan Bisnis Keluarga Vs Bisnis Non-keluargaunclassified
“…However, having job autonomy alone may not be sufficient to motivate nonfamily employees (Block et al , 2016; Tabor et al , 2018). Various studies have demonstrated the additional motivational significance of nonfamily employees' emotions (Bernhard and O'Driscoll, 2011; Ramos et al , 2014; Sieger et al , 2011) and attitudes (Ferraro and Marrone, 2016; Flamini et al , 2020; Medina-Craven et al , 2020) in driving their pro-organizational attitudes. Accordingly, in this particular study we suggest that nonfamily employees' job autonomy may serve to heighten their work passion, which in turn may influence their pro-organizational attitudes.…”
Section: The Mediating Role Of Nonfamily Employees' Work Passionmentioning
confidence: 99%
“…Due to an insufficient number of able, willing and committed family employees (Chua et al , 2009; De Massis et al , 2008), many family-small-to-medium-sized enterprises (SMEs) rely on the unique knowledge, skills and social capital of their nonfamily employees (Lingo and Elmes, 2019; Ramos et al , 2014; Sieger et al , 2011) to achieve specific development goals (Ensley, 2006). However, prior research has recognized that the specific characteristics of family enterprises such as paternalistic–autocratic rule, founder-centric cultures, lack of delegation, ingroup–outgroup perceptions, altruism and nepotism (Barnett and Kellermanns, 2006; Medina-Craven et al , 2020) can significantly influence nonfamily employees' turnover intentions and job satisfaction (Ferraro and Marrone, 2016; Flamini et al , 2020; Sieger et al , 2011; Tabor et al , 2018). Nonfamily employees who are satisfied with their jobs and who are less likely to quit, are more likely to be willing to go the “extra-mile” to help the family enterprise and are thus considered essential to enterprises success and survival (Barnett and Kellermanns, 2006; Ramos et al , 2014; Sieger et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations